2005
DOI: 10.1111/j.1600-0846.2005.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Topography and anisotropy of the skin surface with ageing

Abstract: The study of these new parameters will allow objective evaluation of the action of topical dermatological and cosmetic treatment, and new techniques in plastic surgery (e.g. laser resurfacing), and will enable the accurate follow-up of certain pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 5 publications
(3 reference statements)
5
74
0
Order By: Relevance
“…These results are in general agreement with previous observations which involved the anatomical site at the eye corner [4] and 2 sites, forearm and back of hand [5] or forearm and temple, in 2 age groups [3]. A study differentiating only between young and aged adults but including numerous sites (lower leg and thigh, abdomen, lower and upper back, dorsal, volar forearm and upper arm, and periorbital area) concluded that the age effect on roughness is dependent on site, although some confounding between intrinsic aging and photoaging occurred [8].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in general agreement with previous observations which involved the anatomical site at the eye corner [4] and 2 sites, forearm and back of hand [5] or forearm and temple, in 2 age groups [3]. A study differentiating only between young and aged adults but including numerous sites (lower leg and thigh, abdomen, lower and upper back, dorsal, volar forearm and upper arm, and periorbital area) concluded that the age effect on roughness is dependent on site, although some confounding between intrinsic aging and photoaging occurred [8].…”
Section: Resultssupporting
confidence: 83%
“…Skin micro-relief and wrinkles are manifestations of different etiology which in combination produce the overall skin roughness [1,2]. Roughness was found to be greater in aged compared to young skin at different anatomical sites including volar forearm, back of the hand, periorbital area, and temple [3,4,5,6], while results were conflicting for the lower leg [7]. Roughness was reported to vary significantly between different sites, being largest in the posterior neck and smallest in the upper back and lower leg, while only minor differences between genders and races were shown [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polyurethane-coated polyamide microfibre fleece (Lorica soft Ò , Lorica Sud, Milan, Italy) showing a surface topography and roughness similar to that of human skin ( Table 2) was chosen as a model substrate [15,22,29,30]. Pump vapouriser bottles (Type 215-6274, VWR, Dietikon, Switzerland) were used to manually spray the lipid mixtures onto the substrates, as described in detail in [31].…”
Section: Skin Model Substrate and Film Preparationmentioning
confidence: 99%
“…The most used techniques for measuring skin surface topography was the skin surface replicas analysis [3]. Although the replica analysis had advantages, they had many disadvantages which limit these methods for skin assessment.…”
Section: Introductionmentioning
confidence: 99%